2016
DOI: 10.1371/journal.pone.0160371
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Glutinous Rice Flour by Dry-Heat Treatment

Abstract: Glutinous rice flour (GRF) and glutinous rice starch (GRS) were modified by dry-heat treatment and their rheological, thermal properties and freeze-thaw stability were evaluated. Compared with the native GRF and GRS, the water-holding ability of modified GRF and GRS were enhanced. Both the onset and peak temperatures of the modified samples increased while the endothermic enthalpy change decreased significantly (p < 0.05). Meanwhile, dry heating remarkably increased the apparent viscosities of both GRF and GRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…2. A similar result was published by Qin et al (2016), and they found that dry heating increased the viscosity of rice flour. The loss modulus (G″) represented the viscous characteristics and the capacity of the dough to resist flow.…”
Section: Rheological Behaviours Of Doughsupporting
confidence: 85%
See 4 more Smart Citations
“…2. A similar result was published by Qin et al (2016), and they found that dry heating increased the viscosity of rice flour. The loss modulus (G″) represented the viscous characteristics and the capacity of the dough to resist flow.…”
Section: Rheological Behaviours Of Doughsupporting
confidence: 85%
“…The improvement of G ″ reflected that heat treatment caused increase in the viscosity of mixed dough. A similar result was published by Qin et al (2016), and they found that dry heating increased the viscosity of rice flour. HTHP treatment and steaming treatment significantly increased the viscosity in mixed dough with yeast, while the viscosity in mixed dough with Laomian all improved for three heat treatments methods and was in order of mRFh > mRFs > mRFe > mRF > WF.…”
Section: Rheological Behaviours Of Doughsupporting
confidence: 85%
See 3 more Smart Citations